Strategi Penanganan Pembiayaan Bermasalah pada BMT Masyarakat Madani Sumatera Utara: Analisis SWOT - Imsar; Agung Ramadhan Trapoltanta Pratama; Rahmi Syahriza (Universitas Muhammadiyah Surabaya, 2023)
Abstract The aim is to analyze the handling of problematic financing at the BMT of the Madani Society of North Sumatra. Using qualitative methods with data analysis techniques using SWOT methods (Strength, Weakness, Opportunity, Threat). Data collection techniques used are observations, interviews, questionnaires and documentation. The results of this study are: (1) Problematic financing in BMT Northern Sumatra's Madani community is caused by internal factors such as quantitative human resource constraints, lack of support for digital and modern technology systems and the continuing instability of the labour force. While external factors are caused from the continuously deteriorating member economy, the abuse of funding funds by members and financial institutions of banks also conduct microfinancing. (2) The results of the calculations of the IFE and EFE matrix indicate that BMT Madani Society is in the quadrant II, which is a position that marks a strong company, but faces a major threat. So BMT Madani Society of North Sumatra is recommended to pursue a diversification strategy that is to optimize strengths to minimize existing threats. Key words : Management Strategy, Problematic Financing, SWOT